Uma análise semiótica discursiva de II João - Humberto Marcos Balaniuc (2023)
Being the Sacred Scriptures a constant source of analysis by different theories of interpretation and being it an unquestionable basis of Western culture and perhaps worldwide, this dissertation proposes to analyze a selection of a biblical text - the Second Letter of John - through Greimasian discourse semiotics, having as main references the theoreticians Diana Luz Pessoa de Barros and Denis Bertrand. The objective of the work is to demonstrate the relevance of Greimasian semiotics as a theoretical instrument to extract from the scriptural text its opinion of signification, since semiotics has as its object, as a science, the "seem of meaning" (BERTRAND, 2003, p.11). The semiotic analysis occurs through the generative path of meaning, in which the text is analyzed on three levels: discursive, narrative and fundamental, with each level presenting its own syntax and semantics. The semiotic analysis proposed is based on a translation made by the author of this work based on the Greek text koinê from II John. For this, a grammatical analysis of each word of the Greek text was made, in addition to the construction of a syntactic diagram in which the syntactic relations of the Greek text can be better visualized. It is proposed that the making of the diagram also helps in the proposed semiotic analysis insofar as the structuring of the Greek text is revealed to the interpreter's eyes. The analysis of the meaning of the text is being demonstrated in each layer of meaning of the generative path, in which its constitutive elements are being exposed throughout the work. Finally, we try to demonstrate that, in fact, Greimasian semiotics collaborates in the process of extracting meaning from the biblical text. In the appendices, we offer a brief analysis of the text by means of Peircian semiotics with the purpose of opening a theoretical path for textual analysis by means of this semiotics, besides the presentation of a figure with a manuscript of II John. Key-words: Semiotics, Bible, Greimas